2019
DOI: 10.1177/1753193419851775
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cup orientation on stability of trapeziometacarpal total joint arthroplasty: a biomechanical cadaver study

Abstract: It has been suggested that the cup of a trapeziometacarpal total joint replacement should be positioned parallel with the proximal articular surface of the trapezium to align it with the centre of motion. This would diminish the chance of dislocation. The goal of this study was to test this idea biomechanically. A linked trapeziometacarpal prosthesis was implanted in seven cadaver hands and combined with three-dimensional printed trapezium cups in 17 different orientations. For every combination, stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
0
10
0
5
Order By: Relevance
“…Caekebeke et al performed thumb CMC arthroplasty by placing a cup parallel to the proximal articular surface of the trapezium and reported a survival rate of 96% at a mean of 65 months ( Caekebeke and Duerinckx, 2018 ). Blauns et al studied which cup angle prevents dislocation using ARPE ball-and-socket implants and fresh cadavers ( Brauns et al, 2019 ). They confirmed that it is important to place a cup parallel to the proximal articular surface of the trapezium, as Duerinckx mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caekebeke et al performed thumb CMC arthroplasty by placing a cup parallel to the proximal articular surface of the trapezium and reported a survival rate of 96% at a mean of 65 months ( Caekebeke and Duerinckx, 2018 ). Blauns et al studied which cup angle prevents dislocation using ARPE ball-and-socket implants and fresh cadavers ( Brauns et al, 2019 ). They confirmed that it is important to place a cup parallel to the proximal articular surface of the trapezium, as Duerinckx mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various reasons for dislocation and loosening, such as fracture of the trapezium, metallosis, mechanical impingement between the prosthetic neck and the cup, or imperfect cup placement ( Facca and Liverneaux, 2012 ; Vitale et al, 2013 ; Brauns et al, 2019 ), it is important to place prostheses in the correct position ( Duerinckx and Caekebeke, 2016 ; Cootjans et al, 2017 ) and restore normal CMC joint kinematics ( Lerebours et al, 2020 ) using a prosthesis in order to prevent complications, such as loosening or dislocation of the prosthesis ( Lerebours et al, 2020 ). However, the surgical methods for placement of prostheses are based on expert experience ( Duerinckx and Caekebeke, 2016 ) and the optimal position for the implant has not yet been determined ( Brauns et al, 2019 ). In addition, it is often said that replacing the CMC joint with a single center of rotation (COR) is very difficult without changing the normal thumb CMC kinematics because the original saddle joint has a variable COR ( de Raedt et al, 2013 ; Huang et al, 2015 ; D'Agostino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates an even bone fringe around the cortical fixed cup base with symmetric rim support, which is difficult with an irregularly sized and saddle-shaped joint surface. Furthermore, alignment with the central axis of the trapezium perpendicular to the scaphotrapezial trapezoidal joint is recommended (Brauns et al., 2019; Duerinckx and Caekebeke, 2016). For cancellous cup insertion, a correct saw cut perpendicular to the central axis of the trapezium – rather than perpendicular to the TMC joint surface – is important in order to align the cup on the central trapezium axes.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanische Studien haben gezeigt, dass eine vermehrte dorsale Inklination der Pfanne das Luxationsrisiko erhöht. Dies gilt gleichermaßen, wenn die mediale und laterale Inklination 20°übersteigt [4]. Im Zweifelsfall erfordert dies das nochmalige Ausschlagen der Pfanne und die Neupositionie- Nach der für die primäre Stabilität wichtigen Kapselnaht erfolgt der schichtweise Wundverschluss und die Anlage einer dorsoradialen Daumengipsschiene.…”
Section: Eine Operationstechnik Mit Akzeptabler Lernkurveunclassified